2016
DOI: 10.18632/oncotarget.7034
|View full text |Cite
|
Sign up to set email alerts
|

PDIP46 (DNA polymerase δ interacting protein 46) is an activating factor for human DNA polymerase δ

Abstract: PDIP46 (SKAR, POLDIP3) was discovered through its interaction with the p50 subunit of human DNA polymerase δ (Pol δ). Its functions in DNA replication are unknown. PDIP46 associates with Pol δ in cell extracts both by immunochemical and protein separation methods, as well as by ChIP analyses. PDIP46 also interacts with PCNA via multiple copies of a novel PCNA binding motif, the APIMs (AlkB homologue-2 PCNA-Interacting Motif). Sites for both p50 and PCNA binding were mapped to the N-terminal region containing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(54 citation statements)
references
References 84 publications
(134 reference statements)
1
53
0
Order By: Relevance
“…The PCNA binding of PDIP46 is due to its possession of a cluster of 5 APIM motifs [56]. The APIM (AlkB homologue 2 PCNA-Interacting Motif) is a novel PCNA binding motif that was first identified in the human DNA repair enzyme oxidative demethylase ABH2 (AlkB homologue 2) [147].…”
Section: Mapping Of the Interaction Sites Between Pdip46mentioning
confidence: 99%
See 4 more Smart Citations
“…The PCNA binding of PDIP46 is due to its possession of a cluster of 5 APIM motifs [56]. The APIM (AlkB homologue 2 PCNA-Interacting Motif) is a novel PCNA binding motif that was first identified in the human DNA repair enzyme oxidative demethylase ABH2 (AlkB homologue 2) [147].…”
Section: Mapping Of the Interaction Sites Between Pdip46mentioning
confidence: 99%
“…This has been demonstrated by their co-immunoprecipitation and co-elution during affinity chromatography on immobilized anti-p125 monoclonal antibody. ChIP analysis with antibody against the p125 subunit showed that PDIP46 was present together with two components of the mammalian replisome [56]. These are Mcm2, a component of the CMG (Cdc45-MCM-GINS) helicase [151], and Ctf4, which associates with CMG [152,153].…”
Section: Evidence That Pdip46 Is Associated With Pol δ In Vivomentioning
confidence: 99%
See 3 more Smart Citations